ChemInform Abstract: Synthesis of Novel Carbohydrate‐Based Valine‐Derived Formamide Organocatalysts by CuAAC Click Chemistry and Their Application in Asymmetric Reduction of Imines with Trichlorosilane. Issue 17 (April 2015) - Ge, Xin; Qian, Chao; Chen, Xinzhi
Abstract The applied catalyst can be recycled and reused at least five times.